The implementation of summarizing strategy on students’ reading comprehension - Taqiyuddin .Taqiyuddin (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This research studied to investigate whether there was a significant difference between making summarizing Strategy and without making summarizing Strategy on Students? Reading Comprehension at MAN Batam. The participant was tenth-grade students of MAN Batam, and the object of this research was the Implementation of using Summarizing Strategy on Students’ Reading Comprehension. The design of this research was a Quasi-Experimental Research, with Non-Equivalent Control Group Design. Class A consisted of 30 students as an experimental class and class B consisted of 30 students as a control class. So, the total of samples was 60 students. To analyze the data, the researcher used an independent sample t-test formula by using the software SPSS 20.00 Version. After analyzing the data, the researcher found that there was a significant difference between using summarizing Strategy and without using summarizing strategy on students? reading comprehension of the tenth-grade students at MAN Batam, where T shows 0.083 at a significance level of 5% it shows 2.00, and at the level of 1%, it shows 2.62. Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted which shows 2.00<0.086>2.65. In conclusion, there is a significant difference in students? reading comprehension at the tenth-grade students of MAN Batam.